Inside the minds of psychodynamic psychotherapist fathers: An exploration of psychotherapists’ experiences of fatherhood - Glover, Christopher Clive (My University, 2020)
Abstract The journey of becoming a psychodynamic psychotherapist involves rigorous training aimed at facilitating the internalisation of perspectives and values that inform particular identity performances. The identity of a psychotherapist is constructed to shape a particular manner of engaging with others and oneself. Some of the most deeply pervasive conceptual tenets within the body of psychodynamic theory surround theories and discourses with fairly prescriptive ideas concerning the role of the parent in facilitating the healthy psychological and emotional development of the child, as well as the consequences of deviating from these prescriptions. No research has been conducted with psychotherapist fathers and their perspectives on how the psychotherapist identity may interact with the identity of father in shaping the experience and performance of fathering. As such, exploring the experiences of psychotherapist fathers may offer a unique perspective into the experience of fathering. This study explores how these identities interact in shaping the experiences of psychotherapist fathers and how this may influence their particular performances of fathering. The results of this study suggest that the collocation of these identities broadly emphasises that ideal fathering needs to involve investment in facilitating the development of the child. Additionally, contradictory messages from theory and society ideas appear to result in tensions within the performance of ideal fathering, particularly with regards to negotiating between nurturing and separating roles. Feelings of envy and rivalry appeared to be largely disavowed, possibly due to the sense that they were dystonic with the values embedded within their collocated identities.
A research project submitted in partial fulfilment of the requirements for the degree of MA Clinical Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg,